2022
DOI: 10.3390/ijms23126806
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Metastasis: Mechanisms and Therapeutic Implications

Abstract: Breast cancer is the most common malignancy in women worldwide. Metastasis is the leading cause of high mortality in most cancers. Although predicting the early stage of breast cancer before metastasis can increase the survival rate, breast cancer is often discovered or diagnosed after metastasis has occurred. In general, breast cancer has a poor prognosis because it starts as a local disease and can spread to lymph nodes or distant organs, contributing to a significant impediment in breast cancer treatment. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 123 publications
2
72
0
Order By: Relevance
“…EMT is one of the critical mechanisms in breast cancer metastasis [ 5 , 40 ]. Abnormal regulation of EGFR signaling in tumors usually leads to changes in cell proliferation and adhesion, increasing cell aggressiveness and motility, which are hallmarks of EMT and the initial stages of tumorigenesis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMT is one of the critical mechanisms in breast cancer metastasis [ 5 , 40 ]. Abnormal regulation of EGFR signaling in tumors usually leads to changes in cell proliferation and adhesion, increasing cell aggressiveness and motility, which are hallmarks of EMT and the initial stages of tumorigenesis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis as a representative hallmark of most cancers is primarily responsible for the death from breast cancer [ 3 , 4 ]. It is a cellular process through several mechanisms including epithelial-mesenchymal transition (EMT), by which breast cancer cells cross the surrounding basement membrane and enter the vascular system to spread into distant organs, leading to resistance to therapy and treatment failure [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer metastasis is a highly complicated and multifactorial process, including division from the primary tumor, degradation of the basement membrane from the lumen, invasion into the fibrous stroma surrounding the tumor cells, migration through blood and lymph vessels, and the secondary tumor lesion at a distal tissue. 22,23 Accumulating evidence has shown that invasive breast cancer is frequently associated with the spread of the activated stroma. 24 Myofibroblasts, which are a pivotal component of the tumor microenvironment, directly interact with tumor cells to facilitate the malignant progression of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the annual incidence rate of breast cancer in China has reached 3-4%, and the onset age is reducing, which seriously affects the health and quality of life of female patients (3). Tumor metastasis is an important factor affecting the surgical prognosis of patients with breast cancer, and certain studies have confirmed that 90% of patient mortalities can be attributed to breast cancer metastasis (4,5). Therefore, it is of great importance to further study the mechanisms of breast cancer metastasis and to identify effective targets to inhibit breast cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%